Organizational culture and its relationship to organizational behavior among female secondary school teachers in Hafr Al-Batin - Adil Alshammary; Helwa Alanzi (Umm Al-Qura University, 2022)
The study aimed to reveal the degree of female teachers' awareness of organizational culture from the point of view of the principals of government secondary schools in Hafr Al-Batin, and to determine the statistical differences between the average grades of the study sample about the degree of female teachers' awareness of organizational culture due to academic qualifications and years of service. It also aimed to determine the level of the organizational behavior of female teachers in these schools, and to reveal a statistically significant relationship at the level of significance (α ≥ 0.05) between organizational culture and the teachers' organizational behavior. To achieve the objectives of the study, the descriptive analytical method was used, and its sample consisted of all (45) principals of government secondary schools in Hafr Al-Batin. The study showed that the degree of female teachers' awareness of organizational culture from the point of view of the principals of public secondary schools in Hafr Al-Batin was high (4.24). It also indicated that there were no statistically significant differences between the average scores of the sample members about the degree of female teachers' awareness of organizational culture due to the variable of academic qualification or years of service. The results showed that the degree of practicing organizational behavior among female teachers is high (4.14), as well as innovation and creativity as dimensions related to the degree of organizational behavior practice, their organizational.